Shear strength of a compacted residual soil from unsaturated direct shear tests - Melinda, Fifi. (2008)
The objective of this research was to study the shear strength and volume change characteristics of a compacted residual soil from the Bukit Timah Granitic Formation in Singapore when sheared under constant suction and shearing-infiltration condition. The characteristics of pore-water pressure changes due to water infiltration and the effects of pore-water pressure changes on the deformation and the stability of a slope were investigated.